Economic evaluation of integrated care: an introduction - Hindrik Vondeling (International Journal of Integrated Care, 2004)
Background: Integrated care has emerged in a variety of forms in industrialised countries during the past decade. It is generally assumed that these new arrangements result in increased effectiveness and quality of care, while being cost-effective or even cost-saving at the same time. However, systematic evaluation, including an evaluation of the relative costs and benefits of these arrangements, has largely been lacking. Objectives: To stimulate fruitful dialogue and debate about the need for economic evaluation in integrated care, and to outline possibilities for undertaking economic appraisal studies in this relatively new field. Theory: Key concepts, including e.g. scarcity and opportunity costs, are introduced, followed by a brief overview of the most common methods used in economic evaluation of health care programmes. Then a number of issues that seem particularly relevant for economic evaluation of integrated care arrangements are addressed in more detail, illustrated with examples from the literature. Conclusion and discussion: There is a need for well-designed economic evaluation studies of integrated care arrangements, in particular in order to support decision making on the long-term financing of these programmes. Although relatively few studies have been done to date, the field is challenging from a methodological point of view, offering analysts a wealth of opportunities. Guidance to realise these opportunities is provided by the general principles for economic evaluation, which can be tailored to the requirements of this particular field.